KOPI DAPAT MENURUNKAN AKTIVITAS ALT DAN AST SERUM DARAH TIKUS WISTAR ALKOHOLIK - Sara Wijana, I Made; Suranjaya, I Gede; Setyawati, Iriani (SIMBIOSIS, 2018)
Ethanol can damage the liver, indicated by an increase of alanin amino transaminase (ALT) activity and aspartat amino transminase (AST) activity in the blood of alcohol-treated rats. Coffee is rich in antioxidants which are hepatoprotector agent. This study aimed to determine the effect of coffee to reduce alanin amino transaminase (ALT) activity and aspartat amino transminase (AST) activity in blood serum of alcohol-treated rats. The study used 32 male wistar albino rats (200±20g  weight) which were divided into four treatment groups i.e. P0 (negative control which were treated with 1 mL of 30% ethanol/200g body weight (bw)/day), P1 (1 mL of 30% ethanol/200 g bw/day + coffee 0,1g/200g bw in 3,5 mL of water/200 g bw/day), P2 (1 mL of 30% ethanol/200g bw + coffee 0,15 g/200g bw in 3,5 mL of water/200g bw/day), dan P3 (1 mL of 30% ethanol/200g bw + coffee 0,2g/200g bw in 3,5 mL of water/200g bw/day). ALT and AST levels were measured by spectrophotometric method. Data analysis was done by ANOVA followed with LSD test and correlation analysis. The results showed that coffee reduced (P<0.01) the activities of ALT and AST of rats blood serum. ALT and AST activities were significantly different (P<0.01) among treatments and with control. Dose of coffee was negatively correlated with ALT activity with correlation coefficient (R) -0.978 and AST with correlation coefficient (R) -0.985 (P<0,01). The lowest of ALT and AST activities were found at dose of coffee 0.2 g/200g body weight. Keywords : ethanol , ALT, AST, coffee